Evaluation of Factors Driving Seasonal Nitrate Variations in Surface and Underground Systems of a Karst Catchment - Yue, F. (2020)
The stable isotopes of water and nitrate (δDwater, δ18Owater, δ15Nnitrate, and δ18Onitrate) were used to identify nitrate sources and to assess seasonal variations in hydrological processes affecting nitrate levels. Monthly sampling indicated that nitrate flux is strongly related to agricultural activities and the intensity of rainfall, which can accelerate transport between the surface water (SFW) and underground water (UGW) systems. Nitrate in water samples showed nitrification characteristics and was mainly derived from the oxidation of reductive fertilizers including organic N fertilizer. The isotopic composition of nitrate was affected by denitrification, particularly in the wet season. Isotopic signatures indicate that moderate evaporation occurs during the dry season. Denitrification in underground conduits appears to be relatively minor compared with that in SFW. The results of this study suggest that rainfall is an important factor influencing N flux, which has implications for water management.